¿How bioengineering influences slope stabilization and water erosion mitigation? - Carrasco Rosales , Gabriel Omar (2023)
The objective of the research is to develop a state of knowledge about the use of bioengineering in engineering projects at the national level and in the Latin American region. The influence of the main techniques used is evaluated, evaluating those that include the contribution of the roots of the vegetative material in the Mohr - Coulomb model and the use of the erosion rod and RUSLE methods to estimate the water erosion of a natural slope (slope) unstable. The research is documentary - explanatory with a comparative approach since the value of the safety factor with and without vegetation and the value of current erosion are contrasted using GIS models and the direct method of erosion nails. It is concluded that the use of vegetation, simply or collectively, to improve and protect unstable soils, influences the value of the safety factor, substantially increasing, and minimizing the amount of eroded soil.